Money and how to make more of it - Chase, Lorraine (Orion Business Books, 1998)
TV Presenter Adam Shaw and Actress Lorraine Chase cut through the ' jargon' of money to provide a beginner guide to investment and savings. The no of shareholders in the UK will increase from 10 million to nearerto 20 million, as building societies pay out shares and cash to their members from flotation. Many of these members will have little or no knowledge of investment and the stock market. This book, by TV financial broadcaster Adam Shaw and actress Lorraine Chase, is a beginners guide to money and how to invest and save it. Written and presented in a user friendly and entertaining way, the authors cut through the jargon and explain the key elements to making your money grow, including the stock market, financial press, risky and safe investments, PEP's, TESSA's, Pensions, Bonds, currencies, and the characters and institutions of the financial world.